Effect of the computer-aided static navigation technique on the accuracy of bicortical mini-implants placement site for maxillary skeletal expansion appliances: an in vitro study - Paulina Rodríguez Torres; Elena Riad Deglow; Álvaro Zubizarreta-Macho; Georgia Tzironi; Héctor González Menéndez; Juan Lorrio Castro; Ana Belén Lobo Galindo; Sofía Hernández Montero (BMC, 2023)
Abstract The objective of the present study was to evaluate and compare the effect of the computer-aided static navigation technique on the accuracy of the maxillary skeletal expansion (MSE) appliances. Material and Methods: Forty orthodontic self-drilling mini-implants were placed in ten anatomically based standardized polyurethane models of a completely edentulous upper maxilla, manufactured using a 3D impression procedure. The four orthodontic self-drilling mini-implants for anchoring the MSE appliance were digitally planned on 3D planning software, based on preoperative cone-beam computed tomography (CBCT) scan and a 3D extraoral surface scan. Afterwards, the surgical templates were virtually planned and manufactured using stereolithography. Subsequently, the orthodontic self-drilling mini-implants were placed an postoperative CBCT scans were performed. Finally, coronal entry-point, apical end-point and angular deviations were calculated using a t-test for independent samples or a non-parametric Signed Rank test. Results: Statistically significant differences were not shown at coronal entry-point (p = 0.13), apical end-point (p = 0.41) and angular deviations (p = 0.27) between the planned and performed orthodontic self-drilling mini-implants. Conclusions: Computer-aided static navigation technique enables accurate orthodontic mini-implant placement for the MSE appliances.